THROMBOCYTOPENIA AMONG TRAUMA PATIENTS ADMITTED IN ICU: FREQUENCY AND RELATIONSHIP WITH OUTCOME: Thrombocytopenia Among Trauma Patients - Farukh, Aamir; Ahmad, Ejaz; Baig, Zahid Farooq; Siddique, Umair Ahmad; Tareen, Tariq Bashir; Khan, Aslam (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess the frequency of thrombocytopenia among the patients of trauma at an intensive care unit and to look for its relationship and other socio-demographic factors with the outcome.Study Design: Cross-sectional study.Place and Duration of Study: Intensive Care Unit, Combined Military Hospital Peshawar, from Mar to Aug 2017.Methodology: Thrombocytopenia was defined as platelet count of